1988
DOI: 10.1007/bf01259412
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adjuvant reserpine treatment on catecholamine metabolism in schizophrenic patients under long-term neuroleptic treatment

Abstract: The clinical and biochemical effects of adjuvant reserpine treatment were investigated in 12 chronic schizophrenic patients on long-term neuroleptic medication. The global severity of the symptoms using the Brief Psychiatric Rating Scale did not change significantly in the whole group, however, a moderate decrease in positive symptoms (factors though disturbance, activation and hostile-suspiciousness) was observed for 5 patients. Cerebrospinal fluid (CSF) noradrenaline levels showed a consistent decrease, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…The drugs in group A suppress the activity of NA or DA (or both), whereas the drugs in group B facilitate NA or DA activity (or both). The drugs in group A are known to ameliorate positive symptoms but do not improve negative symptoms . The drugs in group B often exacerbate positive symptoms but have favorable effects on negative symptoms .…”
Section: Does Noradrenergic Dysfunction Exist In Psychiatric Disorders?mentioning
confidence: 99%
See 1 more Smart Citation
“…The drugs in group A suppress the activity of NA or DA (or both), whereas the drugs in group B facilitate NA or DA activity (or both). The drugs in group A are known to ameliorate positive symptoms but do not improve negative symptoms . The drugs in group B often exacerbate positive symptoms but have favorable effects on negative symptoms .…”
Section: Does Noradrenergic Dysfunction Exist In Psychiatric Disorders?mentioning
confidence: 99%
“…The drugs in group A are known to ameliorate positive symptoms but do not improve negative symptoms. 118,[135][136][137][138][139][140][141] The drugs in group B often exacerbate positive symptoms but have favorable effects on negative symptoms. 41,118,[142][143][144][145][146][147][148][149][150][151] In this table, 'chlorpromazine' represents the antipsychotics that block both NA and DA receptors, whereas 'haloperidol' represents the antipsychotics that are thought to block DA receptors selectively.…”
Section: Psychopharmacological Datamentioning
confidence: 99%
“…Reserpine, long recognized to have inherent antipsychotic efficacy (Kline, 1954;Hollister et al, 1955;Barsa et al, 1956), was found as a adjunct treatment to enhance neuroleptic efficacy in some studies (though primarily in non-schizophrenic disorders) (Berlant, 1986;Bagdy etal., 1988). AMPT, which blocks the rate-limiting tyrosine hydroxylase (TH) step in DA synthesis, was consistently reported by Carlsson's group (Carlsson et al, 1972(Carlsson et al, , 1973Walinder et al, 1976;Larsson et al, 1984) to reduce the doses of concurrent neuroleptic treatment needed to maintain antipsychotic efficacy among neuroleptic responders, although other groups did not find comparable effects (Nasrallah et al, 1977).…”
Section: Introductionmentioning
confidence: 99%